THE EFFECTIVENESS OF PAIR WORK IN TEACHING SPEAKING - Fajriani; Melda Wahyuni Patawang (elstic : english language linguistics culture, 2022)
This research was an attempt to find evidence of the influence of the Pair Work Technique on speaking ability. It was conducted at SMPN 2 Sa’dan with a total of 34 students. This study was carried out by Speaking test and Questionnaire in the classroom. It was conducted in 6 meetings. To determine whether the Pair Work Technique for the teaching of speaking was effective, a speaking test was given at the Experimental group in IX-A class to know the students’ speaking ability. The percentage of the students’ speaking ability in Pre-test, namely; 1) 0% students were got excellent, good, and fair category, 2) the percentage of the poor category was 10% (there are 2 students), 3) the percentage of the very poor category was 90% (there are 18 students). And the percentage of the students’ speaking ability in Post-test, namely: 1) the percentage of the excellent category was 0%, but 2) the percentage of the good category was 10% (there are 2 students), 3) the percentage of the fair category was 85% (there are 17 students), 4) the percentage of the poor category was 5% (just 1 student), 5) the percentage of the very poor category was 0%. While to determine whether the Pair Work Technique for the teaching of speaking was effective, a questionnaire was given in the Experimental group to know the students’ motivation. The percentage of the students’ motivation it was found that: 1) the percentage of the strongly motivated classification was 15% (there are 3 students) 2) the percentage of the motivated classification was 75% (there are 15 students) 3) the percentage of the fairly motivated classification was 10% (there are 2 students). It can be concluded that the Pair Work Technique was effective to improve the students’ speaking ability and students’ motivation for the 9th-grade students of SMPN 2 Sa’dan North Toraja in the academic year 2020/2021.